2007
DOI: 10.1016/j.stam.2007.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of interactive effects of synthesis conditions on the characteristics of mesoporous silicas templated using polyoxide surfactant

Abstract: A series of mesoporous silicas (MS-1-MS-9) were synthesized at different gel compositions using a triblock copolymer (TCP), poly(ethylene oxide)-poly(propylene oxide)-poly(ethylene oxide), as the surfactant. The interactive effects of acidity, the contents of tetraethyl orthosilicate (TEOS) and the surfactant, and the gelling temperature on the characteristics of the final material were simultaneously characterized. Increasing acidity favored mesopore formation. A material with a surface area of 760 m 2 /g, mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…It is clearly noted that both samples show the arrays of long-range mesopore channels, which are similar to the image of SBA-15 reported in the literature [3,11,16]. The result suggests that the critical micelle concentration (cmc) was reached or exceeded at a P123:H 2 O ratio of nearly 1:12,000 when the synthesis was conducted at 40 • C. This solution was slightly more dilute than that reported by Kim et al [15] (1:10,700) for a synthesis at 40 • C and Abdullah et al [9] (1:6800) for a synthesis at 60 • C. This suggested that the cmc could be reached at lower P123 concentrations if the synthesis was conducted at lower synthesis temperature.…”
Section: Recovery and Reusability Of Immobilized Lipasesupporting
confidence: 87%
See 2 more Smart Citations
“…It is clearly noted that both samples show the arrays of long-range mesopore channels, which are similar to the image of SBA-15 reported in the literature [3,11,16]. The result suggests that the critical micelle concentration (cmc) was reached or exceeded at a P123:H 2 O ratio of nearly 1:12,000 when the synthesis was conducted at 40 • C. This solution was slightly more dilute than that reported by Kim et al [15] (1:10,700) for a synthesis at 40 • C and Abdullah et al [9] (1:6800) for a synthesis at 60 • C. This suggested that the cmc could be reached at lower P123 concentrations if the synthesis was conducted at lower synthesis temperature.…”
Section: Recovery and Reusability Of Immobilized Lipasesupporting
confidence: 87%
“…Mesoporous SBA-15 was prepared using a sol-gel method as reported earlier [9]. In brief, 150 ml of HCl solution at a concentration of 2.0 M was shaken in an orbital shaker at 40 • C for an hour.…”
Section: Synthesis Of Sba-15 and Amino-functionalized Sba-15 (Fsba-15)mentioning
confidence: 99%
See 1 more Smart Citation
“…This is also evidenced by the reduced orderliness observed from TEM images. In addition, the hydrophobicity of the hydrophilic end (EO) of the surfactant increased; hence, the stretched hydrophilic end becomes curved and moves closer to the hydrophobic end (PO), which makes the micellar particles change from sphere to irregular shape . This eventually leads to irregularities in the shape of the material.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the hydrophobicity of the hydrophilic end (EO) of the surfactant increased; hence, the stretched hydrophilic end becomes curved and moves closer to the hydrophobic end (PO), which makes the micellar particles change from sphere to irregular shape. 46 This eventually leads to irregularities in the shape of the material. Moreover, the sizes of the micellar particles become larger in this process, leading to an augment of the pore size of the synthesized materials, which is consistent with the result of nitrogen adsorption−desorption.…”
Section: Energy and Fuelsmentioning
confidence: 99%